Regional Variation in Pharmacist Perception of the Financial Impact of Medicare Part D - Shamima Khan; Joshua J. Spooner; Harlan E. Spotts (MDPI AG, 2018)
The objective of this study was to perform a nationwide investigation of the financial performance of community pharmacies in the United States since the inception of Medicare Part D. A nationwide, cross-sectional survey of pharmacists was conducted in 2013. The 43-item online survey collected information about demographics, financial implications of Part D on community pharmacy and patients, provision of Medication Therapy Management (MTM) services and opinions about Medicare Part D 2010 updates. The adjusted response rate was 22.3% (419/1885). A majority of respondents (75.6%) reported a stable or increased prescription volume since 2006 but only 40.4% indicated that the financial performance of their pharmacy as either excellent or good during the same period. Owners and part-owners of rural independent pharmacies were more likely to report a below average or poor financial performance (75.0%). The provision of MTM services was not related to the financial performance of the pharmacy. Nearly half (44.7%) of pharmacy owners or part-owners indicated that they were considering selling their pharmacy, with most (94.1%) reporting that their decision to sell was due to the Part D financial pressures. However, the decision to sell was not related to the change in financial performance since 2006 or the volume of prescriptions dispensed.